2019
DOI: 10.32674/jis.v9i2.943
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a Sense of Belonging

Abstract: International students studying at higher education institutions in the United States experience challenges as they adjust to new environments. Social connectedness to American college students could mitigate such challenges and assist international students with social and cultural integration. This study, using qualitative data from interviews, examined international students’ experiences and their sense of belonging on an American college campus, including the factors that contribute to or deter from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…Broadly speaking, most recent research indicated that international students face an array of challenges and difficulties adjusting to the new educational settings (Rivas et al, 2019). However, it has been found that younger students have more difficulties than older ones in making the adjustment.…”
Section: Predictorsmentioning
confidence: 99%
“…Broadly speaking, most recent research indicated that international students face an array of challenges and difficulties adjusting to the new educational settings (Rivas et al, 2019). However, it has been found that younger students have more difficulties than older ones in making the adjustment.…”
Section: Predictorsmentioning
confidence: 99%
“…When faced with a stressful situation, social coping methods involve reaching out to others for support in the hopes that they would offer emotional, practical, or informational assistance. Seeking social support and getting involved in cultural adjustment programs are two instances of social coping methods (Rivas et al, 2019). During stressful conditions, looking to others for assistance, guidance, or emotional solace is what we mean when we talk about seeking social support.…”
Section: Coping Mechanisms For Psychological Adjustmentmentioning
confidence: 99%
“…The purpose of orientation programs is to acquaint incoming overseas students with the culture of the university as well as its regulations, which may include academic prerequisites, grading methods, or campus services. The organization of social events includes activities like cultural festivals, field trips, and mentoring programs that give international students the opportunity to engage with students from various countries and learn about diverse cultures (Rivas et al, 2019).…”
Section: Support Services For International Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing relationship between educational institutions and their students is nicely captured by the notion of student engagement and experience (Bernardo et al, 2012;Kyriakidesa et al, 2019). International students studying at higher education institutions (HEIs) in different countries experience challenges as they adjust to new environments (Rivas et al, 2019). Hence, there is an increasing focus on student experience and improving engagement as a central goal of effective pedagogy (Dunbar and Carter, 2017).…”
Section: Introductionmentioning
confidence: 99%